Episode 17 What Does Pesticide Safety Mean for Organic Farms? With Natalie Hoidal: What's Killing My Kale? - Klodd, Annie; Hoidal, Natalie (My University, 2018)
The December episodes of the podcast center around understanding the complex topic of pesticide use and safety on fruit and vegetable farms, including organic and natural pest management products. The internet lays many claims about the benefits of numerous "alternative" or "natural" remedies for pest management and plant health. How do we know which methods are backed up by science, and which are not? In this episode, Linda lays out ways growers can determine if claims about natural products are accurate and effective. We use epsom salts and compost tea as two examples. Linda is an Extension Educator at Washington State University and manages the Horticultural Myths blog and The Informed Gardener podcast.
Runtime 21:14
Keywords: Pesticides; Organic farming